Pattern formation in the Drosophila embryo: allocation of cells to parasegments by even-skipped and fushi tarazu. - Lawrence, P.A.; Johnston, P. (Development, 1989)
The first sign of metamerization in the Drosophila embryo is the striped expression of pair-rule genes such as fushi tarazu (ftz) and even-skipped (eve). Here we describe, at cellular resolution, the development of ftz and eve protein stripes in staged Drosophila embryos. They appear gradually, during the syncytial blastoderm stage and soon become asymmetric, the anterior margins of the stripes being sharply demarcated while the posterior borders are undefined. By the beginning of germ band elongation, the eve and ftz stripes have narrowed and become very intense at their anterior margins. The development of these stripes in hairy-, runt-, eve-, ftz- and engrailed- embryos is illustrated. In eve- embryos, the ftz stripes remain symmetric and lack sharp borders. Our results support the hypothesis (Lawrence et al. Nature 328, 440-442, 1987) that individual cells are allocated to parasegments with respect to the anterior margins of the eve and ftz stripes.